1996
DOI: 10.1097/00003246-199601000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Causes of hypercarbia with oxygen therapy in patients with chronic obstructive pulmonary disease

Abstract: Changes in physiologic deadspace are sufficient to account for the hypercarbia developed by patients with acute exacerbations of COPD when treated with supplemental oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 10 publications
0
28
0
2
Order By: Relevance
“…[10][11][12][13] The Haldane effect refers to decreased carriage of CO 2 by oxyhemoglobin, and to increased CO 2 release in the presence of oxygen. 11 Hypoxic pulmonary vasoconstriction optimizes the distribution of ventilation/perfusion ratios, and minimizes the physiologic deadspace, improving the efficiency of CO 2 exchange at low FIO 2 .…”
Section: A B Cmentioning
confidence: 99%
“…[10][11][12][13] The Haldane effect refers to decreased carriage of CO 2 by oxyhemoglobin, and to increased CO 2 release in the presence of oxygen. 11 Hypoxic pulmonary vasoconstriction optimizes the distribution of ventilation/perfusion ratios, and minimizes the physiologic deadspace, improving the efficiency of CO 2 exchange at low FIO 2 .…”
Section: A B Cmentioning
confidence: 99%
“…A second potential explanation for the arterial hypercapnia associated with supplemental oxygen administration in this patient group is worsening V /Q mismatch resulting in a significant increase in the dead space-to-Vt ratio. 86,87 V /Q mismatch occurring under these circumstances may be explained as follows. Before supplemental oxygen use, areas of local alveolar hypoxia produce pulmonary hypoxic vasoconstriction, thereby diverting the flow of CO 2 -rich blood from poorly ventilated to better ventilated lung segments.…”
Section: Copdmentioning
confidence: 99%
“…In agreement, Hanson et al 24 and Dick et al 25 concluded that changes in physiologic dead space are sufficient to account for the hypercapnia.…”
Section: Discussionmentioning
confidence: 61%